Persistent but dysfunctional mucosal SARS-CoV-2-specific IgA and low lung IL-1β associate with COVID-19 fatal outcome: A cross-sectional analysis - Ruiz, Maria Julia; Siracusano, Gabriel; Cottignies-Calamarte, Andréa; Tudor, Daniela; Real, Fernando; Zhu, Aiwei; Pastori, Claudia; Capron, Claude; Rosenberg, Arielle R.; Temperton, Nigel; Cantoni, Diego; Liao, Hanqing; et al. (Frontiers in Immunology, 2022)
The role of the mucosal pulmonary antibody response in coronavirus disease 2019 (COVID-19) outcome remains unclear. Here, we found that in bronchoalveolar lavage (BAL) samples from 48 patients with severe COVID-19-infected with the ancestral Wuhan virus, mucosal IgG and IgA specific for S1, receptor-binding domain (RBD), S2, and nucleocapsid protein (NP) emerged in BAL containing viruses early in infection and persist after virus elimination, with more IgA than IgG for all antigens tested. Furthermore, spike-IgA and spike-IgG immune complexes were detected in BAL, especially when the lung virus has been cleared. BAL IgG and IgA recognized the four main RBD variants. BAL neutralizing titers were higher early in COVID-19 when virus replicates in the lung than later in infection after viral clearance. Patients with fatal COVID-19, in contrast to survivors, developed higher levels of mucosal spike-specific IgA than IgG but lost neutralizing activities over time and had reduced IL-1β in the lung. Altogether, mucosal spike and NP-specific IgG and S1-specific IgA persisting after lung severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) clearance and low pulmonary IL-1β correlate with COVID-19 fatal outcome. Thus, mucosal SARS-CoV-2-specific antibodies may have adverse functions in addition to protective neutralization. Highlights Mucosal pulmonary antibody response in COVID-19 outcome remains unclear. We show that in severe COVID-19 patients, mucosal pulmonary non-neutralizing SARS-CoV-2 IgA persit after viral clearance in the lung. Furthermore, low lung IL-1β correlate with fatal COVID-19. Altogether, mucosal IgA may exert harmful functions beside protective neutralization.